METODEBERMAIN GAMBAR SERI SEBAGAI PENGEMBANGAN KEMAMPUAN MENULIS SISWA MI AL-HIDAYAH BANJASARI - Putri, Azzahra Namira; Amelasasih, Prianggi (Universitas Tanjungpura, 2024)
Children who still have difficulty writing because they cannot hold the pencil properly and are not stimulated properly and the absence of parents who encourage them to write at home are other contributing factors. This study aims to describe the use of serial image media in improving the writing skills of grade 4 students at MIAL-Hidayah Banjasari. This research is aqualitative research with a case study approach. The data collection tools in thisstudy are observation sheets, tests, and interview sheets. The results of the study found that the use of series image media in grade 4 MIAL-Hidayah Banjasari can improve student learning activities, students seem to have good motivation, enthusiasm and cooperation in learning. Meanwhile, the teacher factor improves teacher performance and professionalism; Student activities have increased enthusiasm in learning and discussing or collaborating with other students, positive interdependence with other students and activeness in writing superior narrative essays, the use of a series of image media to improve writing skills has increased; The improvement of the ability to write narrative essays using a series of image media in grade 4 students at MIALHidayah Banjasari is categorized as verygood